THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, CURRENT RATIO AND SELF ASSESSMENT ON STOCK PRICES OF CONVENTIONAL BANKING COMPANIES - Devi Dias Pradani; Anny Widiasmara (International Conference on Social and Islamic Studies, 2021)
The state of the economy of a country is claimed to be prosperous when the level of investment in the country always develops from time to time. The importance of implementing CSR in a company is corporate social responsibility which focuses on sustainability on economic, social and environmental aspects. If many investors enter, automatically the stock price in the company will also rise. GCG (Good Corporate Governance) which is by self-assessment can be taken into consideration in determining the company's health level. The purpose of this study is to provide empirical evidence that the current ratio, corporate social responsibility and self-assessment have an effect on stock prices. This type of research is quantitative, secondary data using financial reports, annual reports and closing prices at www.idx.co.id and yahoo Finance. The sample of conventional banking companies used is 20 in 2016-2020. The statistical data analysis technique used in this research is descriptive, multiple linear regression analysis and T test. The results show that CSR and Self-Assessment System variables have a significant effect on stock prices. While the Current Ratio variable has no significant effect on stock prices.